Preliminary study on species authentication in poultry meat products by next-generation sequencing. (March 2023) - Mottola, A.; Piredda, R.; Lorusso, L.; Armani, A.; Di Pinto, A.
Abstract: The growing demand for poultry meat and the complexity of the supply chain affect traceability. Therefore, the aim of this study was to apply DNA metabarcoding to verify the labelling compliance of multi-species poultry meat commercial products. Overall, the molecular identifications conducted in this study confirm that all products contain the species declared in the label and all the non-conformities regard the presence of one or more undeclared meat species. In particular, undeclared species, such as pig and cattle, were highlighted in 8/13 of the samples. Such pattern could be due to technological purposes or accidental contamination linked to inappropriate sanitation practices during processing. However, the presence of undeclared species can affect the ability to choose for consumers with of specific needs (e.g., ethic, religious) or health risk and should be not neglected. Results of this study show that metabarcoding is a promising tool to identify meat species in mixtures. Therefore, its application by food industry and competent institutions, could help to innovate the food management system with the creation of a favorable environment for the protection and respect of the consumer needs. Highlights: NGS Metabarcoding is powerful tool to authenticate multi-species meat products. The presence of unexpected species was highlighted. Undeclared species have ethic and religious implications. Metabarcoding could trace environmental and hygienic-sanitary conditions. Food management system can be improved by the application of advanced approaches.